2016
DOI: 10.2967/jnumed.115.167734
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Characterization of 18F-FLT Uptake with Radioluminescence Microscopy

Abstract: Previous studies of 3'-deoxy-3'-[18F]fluorothymidine (FLT) have only been performed in aggregate, and therefore the single-cell distribution of FLT is unknown. We use a novel in vitro radioluminescence microscopy technique to measure the differential distribution of FLT radiotracer with single cell level precision. Methods Using radioluminescence microscopy, we image the absolute uptake of FLT in live MDA-MB-231 cells grown under different serum conditions, and compare it to fluorescence microscopy of 5-Ethyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…The pattern of binding of [ 18 F]HFB, consisting of preferential binding to fragmented membranes of non-viable cells, has not been observed with other PET radiolabels. Previously, radioluminescence microscopy has been applied to imaging of 9-[4-[ 18 F]fluoro-3-(hydroxymethyl)-butyl]guanine ([ 18 F]FHBG) uptake in HeLa cells expressing herpes simplex type 1 virus (HSV1) thymidine kinase [29], binding of [ 64 Cu]rituximab in single Ramos B lymphocytes [39], uptake of [ 18 F]FDG [30,40] and 3′-deoxy-3′-[ 18 F-]fluorothymidine ([ 18 F]FLT) [41] in MDA-MB-231 cells. In these studies, binding of the radiolabel was only observed in viable cells, with minimal background, ruling out the possibility of a technical artefact.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of binding of [ 18 F]HFB, consisting of preferential binding to fragmented membranes of non-viable cells, has not been observed with other PET radiolabels. Previously, radioluminescence microscopy has been applied to imaging of 9-[4-[ 18 F]fluoro-3-(hydroxymethyl)-butyl]guanine ([ 18 F]FHBG) uptake in HeLa cells expressing herpes simplex type 1 virus (HSV1) thymidine kinase [29], binding of [ 64 Cu]rituximab in single Ramos B lymphocytes [39], uptake of [ 18 F]FDG [30,40] and 3′-deoxy-3′-[ 18 F-]fluorothymidine ([ 18 F]FLT) [41] in MDA-MB-231 cells. In these studies, binding of the radiolabel was only observed in viable cells, with minimal background, ruling out the possibility of a technical artefact.…”
Section: Discussionmentioning
confidence: 99%
“…In a practical demonstration of RLM, 3'-deoxy-3'- 18 F-fluorothymidine ( 18 F-FLT) uptake was imaged in MDA-MB-231 cells grown under different serum conditions and compared to fluorescence microscopy of 5-ethynyl-2'-deoxyuridine (EdU) incorporation in fixed cells, a standard measure of cell proliferation (Fig. 4C) (37). Under serum deprivation few cells (1%) incorporated EdU whereas 18 F-FLT uptake was low, but above background and heterogeneous, with a subset of cells being positive.…”
Section: New Microscopy Opportunitiesmentioning
confidence: 99%
“…Red and green arrows indicate cells with negative and positive signals, respectively. (A–B) and (C) adapted with permission of (36) and (37), respectively.…”
Section: Figurementioning
confidence: 99%
“…The resulting image is intrinsically digital (since it corresponds to the number of detected events) and therefore it can be used to obtain quantitative information on the uptake of a radionuclide in cells. Previously, we have used this technique to characterize cell metabolism based on endpoint and time-dependent transport of glucose 9 , cell proliferation using a radioactive thymidine analog 10 , and drug binding in a humanized mouse model of non-Hodgkin lymphoma 11 .…”
Section: Introductionmentioning
confidence: 99%